Pengajaran Prinsip-Prinsip Ekonomi dalam Pendidikan Dasar sebagai Upaya Menanamkan Jiwa Inovatif - Rifatul Husniah; Aisya Ikrima Bilqis; , Gusmaneli (Jurnal Ekonomi dan Bisnis Digital, 2024)
Introducing economic principles at an early age is crucial for shaping children's understanding of resource management and wise decision-making. This study aims to explore effective teaching methods in economic education at the elementary level, including contextual learning, practical approaches, and the development of problem-solving and entrepreneurial skills. The methods used include literature analysis and relevant case studies. The findings indicate that interactive approaches, such as role-playing and entrepreneurial projects, can enhance students' understanding of economic concepts. Furthermore, parental and community involvement in the learning process also contributes to the development of entrepreneurial values and innovation. Therefore, integrating economic principles into the elementary education curriculum is essential for preparing students to face future economic challenges.